Perancangan Tata Letak Fasilitas Pada Rumah Produksi Taman Eden 100 - El Isma Naomi Thorndike Sihombing; Yosef Manik; Benedikta Anna Haulian Siboro (JISI: Jurnal Integrasi Sistem Industri, 2021)
Small and Medium Enterprise (SME) Taman Eden 100 or CV Andaliman Mangintir is a manufacturing company that produces various andaliman derivative products, including Andaliman Dried Seeds, Andaliman Powder, SikArsik, and Andaliman Seeds. Some of Andaliman's derivative products are already halal certified and some of them do not yet have a halal certificate but already have a PIRT DINKES permit. Thus, it is necessary to have a different room to produce halal products and products that have not been certified halal, so it is necessary to design a layout using the Systematic Layout Planning (SLP) method. The Systematic Layout Planning (SLP) method has several stages in making the layout, namely activity linkage analysis such as Activity Relationship Chart (ARC) analysis, Activity Relationship Diagram (ARD) analysis, and making proposed layouts based on the 5S concept (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). Based on the research conducted, it was found that the total travel time and distance of Material Handling  in the initial layout within 1 month was 3.720 seconds and 2.155 seconds for the time of Andaliman Powder and SikArsik; and 43,69 m and 88,03 m for the distances of Andaliman Powder and SikArsik. By using the Systematic Layout Planning (SLP) method, it is obtained that the total travel time and distance of Material Handling  in the  proposed layout within 1 month is 2.800 seconds and 1.465 seconds for the time of Andaliman proposed layout within 1 month is 2.800 seconds and 1.465 seconds for the time of Andaliman Powder and SikArsik; and 31,28 m and 74.32 m for the Andaliman powders and SikArsik, resulting in a reduction in Material Handling  time and distance of  920 seconds and 12,41 m for Andaliman Powder products; and 690 seconds and 13,71 m for SikArsik products.